Pengaruh Kombinasi Kulit Bawang Merah, Bonggol Pisang Kepok dan Kiambang Sebagai Pupuk Organik Cair Selada Hidroponik - Meiana, Nurma Alya; Jumrodah, Jumrodah; Swestyani, Sondra (Universitas Respati Indonesia, 2026)
Hydroponic techniques are one of the intensification efforts that will ultimately increase the use of land and nutrient solutions. Nutrient solutions use liquid organic fertilizers (POC), which contain the composition of nutrients needed by plants such as AB Mix fertilizer, but are sold at very cheap prices because they are made from fermented organic materials. The organic waste needed in making fertilizer, researchers use red onion skins, banana stems, and kiambang as liquid organic fertilizer because this waste is often found but has not been utilized optimally. The method in this research used a Completely Randomized Design (CRD) which was analyzed using Analysis of Variance, there were 5 treatments P0 (AB Mix 100% Control), P1 (POC 25% + AB Mix 75%), P2 (POC 50% + AB Mix 50%), P3 (POC 75% + AB Mix 25%), P4 (POC 100%). The purpose of this study was to determine the effect of a combination of liquid organic fertilizers of red onion skin, banana stem kepok and kiambang as liquid organic fertilizers for hydroponic lettuce. After conducting experiments and calculations using ANOVA, the results of the effect of the combination obtained the best combination of nutrients in treatment 1, namely 75% AB Mix and 25% POC, with the parameters of leaf width, plant height and the maximum number of leaves